2021
DOI: 10.3390/ijerph182412955
|View full text |Cite
|
Sign up to set email alerts
|

Can Major Public Health Emergencies Affect Changes in International Oil Prices?

Abstract: In order to deepen the understanding of the impact of major public health emergencies on the oil market and to enhance the risk response capability, this study analyzed the logical relationship between major public health emergencies and international oil price changes, identified the change points, and calculated the probability of abrupt changes to international oil prices. Based on monthly data during six major public health emergencies from 2009 to 2020, this study built a product partition model. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 65 publications
(74 reference statements)
0
6
0
Order By: Relevance
“…We further adopt the VIX index and the Economic Policy Uncertainty index (EPU) to depict market and economic uncertainty. Furthermore, studies have shown that public health emergencies combined with many uncertainties can also bring shocks to financial markets (A. Cheng et al, 2021; Liao et al, 2021). Therefore, we select the Infectious Disease Equity Market Volatility Index (EMVID) proposed by Baker et al (2020) as the proxy variable for infectious disease uncertainty.…”
Section: Resultsmentioning
confidence: 99%
“…We further adopt the VIX index and the Economic Policy Uncertainty index (EPU) to depict market and economic uncertainty. Furthermore, studies have shown that public health emergencies combined with many uncertainties can also bring shocks to financial markets (A. Cheng et al, 2021; Liao et al, 2021). Therefore, we select the Infectious Disease Equity Market Volatility Index (EMVID) proposed by Baker et al (2020) as the proxy variable for infectious disease uncertainty.…”
Section: Resultsmentioning
confidence: 99%
“…Albulescu (2020) shows that COVID-19 daily cases of new infections have a negligible impact on long-term crude oil prices, 1 During the recent COVID-19 outbreak, a prolonged period of national lockdown and the shutdown of the manufacturing sector in the majority of countries have also contributed to imbalances in oil production and consumption. Interestingly, Cheng et al (2021) find that abrupt changes in international oil prices are associated with both the H1N1 and COVID-19 pandemics. A Bloomberg report attributes the slowdown in China's jet fuel demand growth to the SARS outbreak (https://www.bloomberg.com/news/articles/2020-01-29/oil-data-from-sars-era-offers-clues-to-impact-ofchina-outbreak#xj4y7vzkg).…”
Section: Introductionmentioning
confidence: 99%
“…The epidemic has had a profound impact on the global economy and welfare, such as business shutdowns, job losses, disrupted supply chains, commodity price volatility, etc. [5][6][7][8]. Moreover, the pandemic introduced risks and challenges to global food and nutrition security [9,10] and made the pathway towards SDG2 even steeper [11], especially in rural areas of the developing world [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%